Enrolled, yet Absent Voices from South-West Delhi - Mehdi, Jayita (Voices of Teachers and Teacher Educators, 2020)
This paper attempts a micro-level understanding of the issue of absenteeism. It is based on a qualitative research study of the factors that adversely affect student attendance. The implications of student absenteeism and the possible ways of addressing the issue are discussed.